Ge2Sb2Se4Te‐Based Optical Switch with Ultra‐High Contrast Ratio by Multilayer Fabry–Perot Cavity - Zhiyang Tang; Chensheng Li; Ruhao Pan; Bo Wang; Yunan Liu; Qianyu Wang; Junhao Tan; Yuan Xiang; Haifang Yang; Junjie Li (Advanced Science)
Abstract Optical switches always desire a high contrast ratio in optical logic circuits and optical communication devices. Although phase change materials are widely applied to design optical switches for their rapid phase change, the high contrast ratio is still hardly achieved for the intrinsic loss of traditional PCMs. Here, the study demonstrates an optical switch with an ultra‐high contrast ratio by introducing the Ge2Sb2Se4Te (GSST) into a multilayer film structure treated as a Fabry–Perot (FP) cavity. The reflectance of the multilayer system can be actively tuned by the phase change of GSST for the FP resonance to achieve an optical switch response. By designing the thicknesses of each layer in the multilayer film, the operating wavelength and the contrast ratio of the switch can be precisely controlled, and an ultra‐high contrast ratio of 2410/735 (simulation/experiment) for the optical switch is constructed in the near‐infrared band. The development of the GSST‐based optical switch paves a new way to realize a high optical contrast ratio and offers a new strategy for high‐performance optical devices.